Desenvolvimento de nanofibras a partir de polímeros reciclados para remoção de metais pesados - Martins, Thiago Rodrigues (2023)
Contamination of water resources by heavy metals and the increasing generation of polymeric waste are aggravating problems in modern society, capable of causing diverse and severe impacts on the environment and human health. Thus, alternatives for the removal of heavy metals from aqueous media and ways to reuse polymeric waste are crucial. This work covers two articles produced on the development of modified polymeric nanofibers for the removal of heavy metals from aqueous solutions. In the first article, recycled expanded polystyrene (EPS) nanofibers were produced using the centrifugal spinning method, followed by modification with chitosan (CS), generating nanofibers called EPS/CS. EPS/CS nanofibers were characterized by scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR). The results of the characterizations showed that the EPS/CS nanofibers had an average diameter of 806 nm, in addition to important functional groups in the adsorption of lead(II). Lead(II) adsorption experiments were performed with these nanofibers, including pH effect, adsorption kinetics, equilibrium isotherms and regeneration tests. The results showed that increasing the pH to 6 favored the removal of lead(II). The pseudo-second order model best fitted the kinetic data, while the AranovichDonohue model best described the equilibrium data, with the nanofibers presenting a maximum adsorption capacity of 137,35 mg g-1 . Thermodynamic parameters indicated a spontaneous, favorable, and endothermic process. After four cycles, the nanofibers maintained 63,04% of their original adsorption capacity. In another article discussed in this work, recycled polyethylene terephthalate (PET) nanofibers were modified with tannin (TN) using the centrifugal spinning method, generating nanofibers called PET/TN. After a crosslinking step with glutaraldehyde, the PET/TN nanofibers were also characterized by SEM, TGA and FTIR. The characterization results showed that the PET/TN nanofibers had an average diameter of 188 nm, in addition to functional groups that were crucial for lead(II) adsorption. Lead(II) adsorption experiments were also performed with these nanofibers, including pH effect, adsorption kinetics, equilibrium isotherms, and regeneration tests. The results showed that increasing the pH to 6 favored the removal of lead(II). The pseudo-first order model best fitted the kinetic data, while the Sips model best described the equilibrium data, with the nanofibers presenting a maximum adsorption capacity of 350,81 mg g-1 . Thermodynamic parameters indicated a spontaneous, favorable, and endothermic process. After four cycles, the nanofibers maintained 45.20% of their original adsorption capacity. The results of both articles point to recycled polymer nanofibers as excellent alternatives to heavy metal adsorption, in addition to reducing the disposal of polymeric waste in the environment, generating aggregated value nanomaterials.